Simulation of C and N in the soil microbial biomass after straw Incorporation into soil - Agostini, Francesco; Sholefield, Paul (Italian Journal of Agronomy, 2006)
Straw incorporation into soil seems to limit N leaching as well as improving soil structure and contributing to C storage in soil. A better understanding of its effect on the dynamics of soil N can be reached using a model simulating C and N contents in soil biomass. A simple model has been developed modifying the sub-routine of crop residue decomposition implemented in the SUNDIAL package. The updated model calculates daily N and C in microbial biomass, using an increased number of pools with different decomposition rates in order to simulate the differentiate decomposition carried out by soil fungal and bacterial populations. The model has been calibrated using results of a laboratory experiment, and then validated using published data from a field experiment on straw incorporation. In both cases soil moisture content and temperature has not been taken into account to carry out a more robust evaluation. The new model, which uses composite pools instead of single pools to describe the residual and the microbial biomass pools, can more accurately predict C and N contents in microbial soil biomass shortly after straw incorporation; however it is still inaccurate in simulating longer scenarios (365 days). The work presented here shows how even a semi-empirical model such as SUNDIAL when properly modified can simulate the effect of straw incorporation, however further work is required to determine a possible microbial and or chemical justification for the empirical splitting of the decomposition pool.